Mechanistic Understanding of Antioxidants Impact on Cognitive Function in Geriatric Canines - Lauren R. Thomas; Hayley A. Booth; Kaleigh E. Beane; Kristopher A. Bottoms; Sami Dridi (Advances in Food Technology and Nutrition Sciences, 2018)
Canine cognitive dysfunction syndrome (CDS) is a collection of symptoms, or behavioral changes, described specifically in dogs of advanced age unrelated to any other diagnosable ill-ness. Symptoms may include an altered sleep-wake cycle, newly developed destructive behavior, inappropriate elimination, excessive vocalization, pacing or wandering, and altered social interaction with the owner.